Dissolved Core Alginate Microspheres as “Smart-Tattoo” Glucose Sensors - Chaudhary, Ayesha (2009)
The feasibility of multilayer thin film coated dissolved-core alginate-templated microsphere sensors based on fluorescence resonance energy transfer and competitive binding, was explored in simulated interstitial fluid, using glucose as a model analyte. The glucose sensitivity was observed to be 0.89%/mM glucose with a linear response in the range of 0–50mM glucose. The sensor response was observed to be completely reversible in nature with a response time of 120 seconds. The system was further demonstrated to respond similarly using near-infrared dyes (Alexa Fluor-647-labeled dextran as donor and QSY-21-conjugated apo-GOx as acceptor) which exhibited a sensitivity of 0.94%/mM glucose with a linear response in range of 0–50mM glucose, making the sensor more amenable to in vivo use, when implanted in scattering tissue.